When good intentions are not enough … Insights on networks of "paper park" marine protected areas. Issue 3 (14th December 2012) - Rife, Alexis N.; Erisman, Brad; Sanchez, Alexandra; Aburto‐Oropeza, Octavio
Abstract In efforts to protect the world's oceans, the Convention on Biological Diversity has moved the goal of establishing marine protected areas (MPAs) to cover 10% of the ocean from 2012 to 2020. This adjustment suggests that the rush to establish MPAs without proper resources does not resolve conservation problems. In fact, such actions may create a false sense of protection that camouflages degradation of marine ecosystems on regional scales. To exemplify this phenomenon, we reviewed MPA efficacy in the Gulf of California, Mexico, where some 23, 300 km2 have been decreed as MPAs. With the exception of Cabo Pulmo National Park, MPAs have not met conservation or sustainability goals. We examined MPA budgets and foundations' investment in the region and found that funding for management is not the limiting factor in MPA efficacy, although funding for enforcement may be deficient. We conclude that MPAs have failed because of insufficient no‐take zones, lack of enforcement, poor governance, and minimal community involvement. We need a new philosophy to implement MPAs to take advantage of the scientific knowledge and monetary investment that have been generated worldwide and ensure that they complement effective fisheries management outside their borders.